Meliponiculture for Income Generation - S Suroshe, Sachin; Chauhan, Avinash; KM, Kumarnag (Indian Journal of Plant Protection, 2025)
Meliponiculture is the rearing and management of stingless bee (SB) for honey and other hive products, besides pollination. SBs are highly developed social insects living in colonies found in all sub-tropical and tropical regions of the globe with more than 500 described species belonging to the order Hymenoptera and family Apidae. It has a sting but significantly reduced and cannot be used for defence. SBs are important pollinators and close relatives of honey bees and bumblebees. SBs are very important for their role in primary health care through production of medicinal hive products such as honey, propolis and bee bread. Like honey bee, it resides in cavities with a queen (only egg laying female), workers (sterile females) and drones (males). In India, SB, Tetragonula iridipennis is present in low altitudes while, Lepidotrigona ventralis is present in higher altitudes. The colonies of SBs are perennial in nature and usually consist of hundreds or thousands of workers. Although, nesting habits are variable, most of the SB species build their nests in several substrates such as, subterranean cavities, tree trunks, rock crevices, brick walls, abandoned termite nests, arboreal ant nests and subterranean chambers abandoned by ants. After the pupation, the sealed cells can be differentiated on the basis of appearance. The duration of different life stages of different castes in T.iridipennis is 47-51 days for queens, 49-54 days for workers and 52-55 days for drones. The ratio of workers to males is in the range of 3-7 % drones/colony. SB provides different high value hive products such as honey, wax, propolis and bee brood. Besides, it also provides pollination services to different crops resulting in increased crop productivity and production. These also maintain ecological biodiversity by rendering pollination services. In different states like Nagaland, Kerala, Tamil Nadu, beekeepers could increase their income by adopting Meliponiculture as a part time and then full time profession. The highly medicinal valued hive products of SB viz., honey (Rs. 2500-5000/kg), wax (Rs. 1000-2000/kg), perennial colony behaviour, amenable to less maintenance and easy to handle makes it beekeepers friendly for setting a profitable venture. The pollination potential of SB on different crops has been worked out with positive results leading to increased production and quality under the both protected and open field conditions. Besides producing hive products, SB also provide a great scope for the organic production of crops as these are capable of performing pollination under protected conditions where other bees do not work. So, for realizing the full potential of SB, the scientific rearing and management along with the awareness of its role is very much important.